Workshop for Increasing the Capability of Teachers and Educational Personnel in Teaching Factory Learning - Rismawati Rismawati (TGO Journal of Community Development, 2024)
This activities is based on the low capability of teachers in implementing the learning process with the teaching factory model at SMK Muhammadiyah Kutowinangun. The appropriate teaching factory learning approach used at SMK Muhammadiyah Kutowinangun because it produces competent and work-ready graduates. The purpose of this research is to improve teacher capability to be more productive in implementing learning with the teaching factory approach. The focus of this research is on productive teachers at SMK Muhammadiyah Kutowinangun. The challenges of this research experienced by teachers because they are required to leave the teacher-centered learning strategy to the student-centered learning strategy. This school action research was carried out in two cycles in each cycle through the stages of planning, implementation, observation and reflection. The results of this study obtained a value with an average of 94 (A) and a percentage of completeness of 91.67%. With this training, productive teachers at SMK Muhammadiyah Kutowinangun are able to implement teaching factory learning better. The conclusion of this research is that the workshop carried out is expected to be able to provide an increase in the capability of teachers and educators in the learning process using the teaching factory learning model.